Urbanization shapes West African diets throughout the rural-urban continuum - Cockx, Lara; Boti, Bolou Bi David (Elsevier, 2025)
Our understanding of how urbanization interacts with food consumption has been hindered by the lack of a unified definition of what constitutes an “urban” area. The use of a binary designation also fails to capture the complexity and diversity of settlement types and results in a focus on the “rural-urban divide”. This study combines nationally representative survey data on household food consumption from eight West African countries with geospatial data capturing the urbanization gradient following the global definition of the Degree or Urbanization. This allows us to analyse consumption of different food groups, diet quality, and macronutrient intakes throughout the rural-urban continuum. We find robust evidence of an increasing rural-urban gradient in total food consumption, as well as a gradual shift away from traditional staple foods, towards increased consumption of foods that require less or no preparation. Residing in more urbanized areas is associated with greater diet diversity and increased consumption of vegetables and animal-source foods. Yet, rising intakes of unhealthy foods and fats in particular along the rural-urban continuum contribute to a deterioration of diet quality. While the estimated effects are strongest in cities, these diet transitions also take place in peri-urban areas and rural areas. This confirms the importance of moving beyond a simple rural-urban dichotomy in research and policy related to food consumption. The demonstrated importance of foods eaten away from home across the entire rural-urban continuum further underscores the need for more research to better understand this sector and explore how it can contribute to both employment and food security.